Utilizing Community through Developing the Center of Community’s Learning Activity (CCLA) in the Rural Area - Rusdiana , A (Asian Journal of Agriculture and Rural Development, 2012)
Utilizing community is an effort to raise their value and status, whose condition nowadays still cannot afford to avoid the trap of poorness and backwardness especially in rural area. In other words, utilizing community is to make them capable and independent, creating more effective and efficient change. The center of community’s learning activity (CCLA) as one of non-formal education institutions grown and established by community’s initiative will develop when both the executor of the program and the stakeholders have similar perception in increasing the quality of community’s life in the condition of marginalization. Therefore, this paper offers ideas of developing CCLA toward independent CCLA, so that CCLA will be more powerful, and finally bring the change for better community.